Peningkatan Profesionalisme Guru melalui Pelatihan Pengembangan Media Pembelajaran Sparkol Videoscribe di Kabupaten Malang - Saiful Amin (Jurnal Pengabdian Pada Masyarakat, 2019)
ENHANCEMENT OF TEACHERS PROFESSIONALISM THROUGH SPARKOL VIDEOSCRIBE LEARNING MEDIA WORKSHOP IN MALANG DISTRICT. The program of activities proposed by the group of KKM 68 and 105 UIN Maulana Malik Ibrahim Malang, in the form of assistance in making sparkol videoscribe learning media. Through these activities, it is expected that the product of the development can add learning resources for teachers and students, and become an encouragement for students in learning. The method used in this service is service learning. Service learning is learning for students based on understanding and the process of recognizing a community. Community service activities in the form of ICT media development workshops can improve the understanding of elementary school teachers in Tulusbesar Village, Malang District in making and using learning media with sparkol videoscribe applications. The products produced in these activities are in the form of learning media in the form of sparkol videoscribe which are interesting in material grades 1 to 6 of elementary school. This service activity received a positive response from teachers as workshop participants.